Tiptop cat - Mader, C. Roger (Boston ; New York : Houghton Mifflin Books for Children, Houghton Mifflin Harcourt, 2014)
A cat finds the courage to climb again after a frightening fall from his owner's apartment balcony.
Keywords: Cats -- Juvenile fiction; Cats -- Fiction